Unbound bilirubin measurements by a novel probe in preterm infants. (18th August 2019) - Hegyi, Thomas; Kleinfeld, Alan; Huber, Andrew; Weinberger, Barry; Memon, Naureen; Shih, Weichung; Carayannopoulos, Mary; Oh, William
Abstract: Background: Hyperbilirubinemia occurs in over 80% of newborns and severe bilirubin toxicity can lead to neurological dysfunction and death, especially in preterm infants. Currently, the risk of bilirubin toxicity is assessed by measuring the levels of total serum bilirubin (TSB), which are used to direct treatments including immunoglobulin administration, phototherapy, and exchange transfusion. However, free, unbound bilirubin levels (Bf) predict the risk of bilirubin neurotoxicity more accurately than TSB. Objective: To examine Bf levels in preterm infants and determine the frequency with which they exceed reported neurotoxic thresholds. Methods: One hundred thirty preterm infants (BW 500–2000 g; GA 23–34 weeks) were enrolled and Bf levels measured during the first week of life by the fluorescent Bf sensor BL22P1B11-Rh. TSB and plasma albumin were measured by standard techniques. Bilirubin-albumin dissociation constants ( Kd ) were calculated based on Bf and plasma albumin. Results: Five hundred eighty samples were measured during the first week of life, with an overall mean Bf of 13.6 ± 9.0 nM. A substantial number of measurements exceeded potential toxic thresholds levels as reported in the literature. The correlation between Bf and TSB was statistically significant ( r 2 0.17), but this weak relationship was lost at high Bf levels. Infants <28-week gestations had more hearing screening failures than infants ≥28-week gestation. Conclusions: Unbound (free) bilirubin values are extremely variable during the first week of life in preterm infants. A significant proportion of these values exceeded reported neurotoxic thresholds.